2021
DOI: 10.1007/s12665-021-09856-4
|View full text |Cite
|
Sign up to set email alerts
|

GIS approach for mapping novel coronavirus in northern state of India, Jammu and Kashmir

Abstract: Novel coronavirus “COVID-19” has affected worldwide. At initial stage, the way out to curb the deadly virus was lockdown, isolating the symptomatic people, quarantining travellers and educating the people about the coronavirus infection so that precautionary measures are followed by people. The present research focuses on the application of Geographic Information System on mapping the coronavirus cases in Jammu and Kashmir. The research attributes the role of dense population and urbanization responsible for i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Similar trends have been shown worldwide where the metropolitan cities and urban areas were affected earlier because of a higher population density, indoor crowding, and high usage of crowded public transport systems ( Lee et al, 2020 ). This has also been supported by GIS mapping conducted in Jammu and Kashmir, which showed that the urban areas are affected first ( Meer and Mishra, 2021 ). A study conducted by Gangwar and Ray (2021) analyzed COVID-19 cases in India using geospatial technology from statistics available in the public domain.…”
Section: Discussionsupporting
confidence: 59%
“…Similar trends have been shown worldwide where the metropolitan cities and urban areas were affected earlier because of a higher population density, indoor crowding, and high usage of crowded public transport systems ( Lee et al, 2020 ). This has also been supported by GIS mapping conducted in Jammu and Kashmir, which showed that the urban areas are affected first ( Meer and Mishra, 2021 ). A study conducted by Gangwar and Ray (2021) analyzed COVID-19 cases in India using geospatial technology from statistics available in the public domain.…”
Section: Discussionsupporting
confidence: 59%
“…Mapping areas with the level of vulnerability to the spread of covid-19 (Meer & Mishra, 2021;Ramadan & Ramadan, 2022;Soni et al, 2022), and its relationship to the multidimensional poverty rate (MPI) (Henao-Cespedes et al, 2022), Air quality measurement during lockdown (Deng et al, 2022), The impact of lockdowns on climate change and the environment through restrictions on human activities on energy use (Madkour, 2022), in the marine sector shows that during the lockdown there was a growth of phytoplankton in the northwest of the Arabian gulf/Persia (Kuwait bay) (Polikarpov et al, 2021), In the health sector such as monitoring the status of Covid-19 infection (Yang et al, 2021), Comparison of Covid-19 infection status between medical personnel and patients (P. , and analysis of industry-based economic sectors through spatiotemporal (Zhou et al, 2021).…”
Section: Figure 1 Bibliometric Keyword Analysis Graphmentioning
confidence: 99%
“…In the social sciences, from spatial and multiscale perspectives, multiple factors influence the virus spread. The pandemic is closely related to urban and dense population areas (Meer & Mishra, 2021 ). Factors of connectivity (Hamidi, Sabouri, & Ewing, 2020 ), mobility, and transportation or even urban design can be identified as factors that facilitate the virus spread, especially in areas with high concentration of jobs, activities, and services (Brizuela, García‐Chan, Gutiérrez, & Chowell, 2021 ; Pérez et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%